Olfactory Stimulation and the Diagnosis of Patients With Disorders of Consciousness: A Double-Blind, Randomized Clinical Trial - Wang, Jing; Zhang, Shaoming; Liu, Wenbin; Zhang, Yao; Hu, Zhouyao; Sun, Ziwei; Di, Haibo (Frontiers in Neuroscience, 2022)
Objectives The aim of this study was to determine whether behavioral responses elicited by olfactory stimulation are a predictor of conscious behavioral response and prognosis of patients with disorders of consciousness (DOC). Methods Twenty-three DOC patients (8 unresponsive wakefulness syndrome [UWS]; 15 minimally conscious state [MCS]) were recruited for this study in which 1-Octen-3-ol (familiar neutral odor) and pyridine were used to test odor behavioral responses, and water was used as an odorless stimulus. One rater presented the three odors in front of each patient’s nose randomly, and another one videotaped all behavioral responses (e.g., pouting, wrinkling nose, slightly shaking head, frowning, etc.). Two independent raters, blind to the stimuli and the patient’s diagnosis, gave the behavioral results according to the recorded videos. One-, 3-, and 6-month follow-up evaluations were conducted to obtain a good prognostic value. Results All MCS patients showed behavioral responses to the 1-Octen-3-ol stimulus; nine MCS and one UWS showed olfactory emotional responses to the pyridine, and two MCS showed olfactory emotional responses to the water stimulus. The incidence of behavioral response was significantly higher using 1-Octen-3-ol than it was for water by McNemar test (p < 0.001), significantly higher using pyridine than it was for water (p < 0.01). The χ2 test results indicated that there were significant differences between MCS and UWS to 1-Octen-3-ol (p < 0.001). For MCS patients, the incidence of behavioral response was no different between using 1-Octen-3-ol and pyridine (p > 0.05). There was no significant relationship between the olfactory behavioral response and the improvement of consciousness based on the χ2 test analysis (p > 0.05). Conclusion Olfactory stimuli, especially for the familiar neutral odor, might be effective for eliciting a conscious behavioral response and estimating the clinical diagnosis of DOC patients. Clinical Trial Registration [https://clinicaltrials.gov/ct2/show/NCT03732092], [identifier NCT03732092].